Effects of probiotic and magnesium co-supplementation on mood, cognition, intestinal barrier function and inflammation in individuals with obesity and depressed mood: A randomized, double-blind placebo-controlled clinical trial - Mahboobi, Sepideh; Ghasvarian, Marzieh; Ghaem, Haleh; Alipour, Hamzeh; Alipour, Shohreh; Eftekhari, Mohammad Hassan (Frontiers in Nutrition, 2022)
Background: the co-occurrence of obesity and mood impairments named as “metabolic mood syndrome” (MMS) is often neglected in the obesity management. This study aimed to evaluate effects of Probio-Tec®BG-VCap-6.5 and magnesium co-supplementation on mood, cognition, intestinal barrier function and serum C reactive protein (CRP) levels in participants with obesity and depressed mood. Design: seventy-four eligible participants were randomly allocated to either Probio-Tec®BG-VCap-6.5 (containing Lactobacillus rhamnosus (LGG®) and Bifidobacterium animalis subsp. Lactis ((BB-12®)) + Magnesium chloride or placebo for 9 weeks. Sociodemographic data were collected in the beginning. Anthropometric, dietary and physical activity (PA) assessments were carried out. Beck Depression Inventory-ІІ (BDI-ІІ) and Montreal Cognitive Assessment (MoCA) scores were assessed through validated questionnaires. Fasting plasma zonulin, lipopolysaccharide (LPS) and (CRP) were measured by ELIZA kits. Results: of seventy-four participants, (mean age 37.51 ± 8.10) ,52 completed the study. Changes in serum LPS and zonulin were not different significantly between groups (-3.04 ± 44.75 ng/dl, 0.11 ± 5.13, ng/dl, p>0.05 for LPS and 1.40 ± 48.78 ng/dl, -0.17 ± 6.60, p>0.05 for zonulin, respectively). CRP levels reduced significantly in intervention group compared to placebo (-474.75 (-1300.00, -125.00) mg/l vs. 175.20 (-957.75, 1683.25) mg/l, p= 0.016). Changes in BDI-ІІ and MoCA scores were not significantly different between intervention (-7.13 ± 5.67, 1.20 ± 2.16, respectively) and placebo (-5.42 ± 6.71, 1.94 ± 1.86, respectively) groups (p>0.05). Conclusion: nine weeks of probiotic and magnesium co-supplementation resulted in decreased CRP levels as an indicator of inflammatory state with no significant effects on mood, cognition and intestinal integrity in individuals with obesity and depressed mood.